2006
DOI: 10.1590/s0102-86502006000600002
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic study of the elbow joint in dog cadavers

Abstract: The elbow arthroscopy in dogs permits detailed intra-articular visualization. The arthroscopic and instrumental portals were simple to be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Superficial iatrogenic cartilage lesions were observed in three specimens in the present study. This result was similar to Van Ryssen's observations but contrasted with Tatarunas's anatomic study in which cartilage lesions were systematically observed (10,14,20). In the present study, a stab incision of the skin, soft tissue, and joint capsule with a number 11 scalpel blade allowed establishment of the arthroscopic portal with a blunt trocar (which differed from Tartaruna's study in which sharp trocars were used).…”
Section: Discussionsupporting
confidence: 88%
“…Superficial iatrogenic cartilage lesions were observed in three specimens in the present study. This result was similar to Van Ryssen's observations but contrasted with Tatarunas's anatomic study in which cartilage lesions were systematically observed (10,14,20). In the present study, a stab incision of the skin, soft tissue, and joint capsule with a number 11 scalpel blade allowed establishment of the arthroscopic portal with a blunt trocar (which differed from Tartaruna's study in which sharp trocars were used).…”
Section: Discussionsupporting
confidence: 88%
“…Postoperative septic arthritis has been reported in 1-3% of arthrotomy cases (7), which is higher than the reported rates of 0.85% following canine arthroscopy (4), 0.9% following equine arthroscopy (8) and 0.8% following human elbow arthroscopy (9). Other complications reported following elective arthroscopy include fluid extravasation, iatrogenic cartilage damage, persistent or worsened lameness and peripheral nerve injury (3,10,11), however their rates of occurrence have not been well defined.…”
Section: Introductionmentioning
confidence: 96%